2002
DOI: 10.1126/stke.2002.160.re15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Growth Factor Receptors by Gangliosides

Abstract: Since their discovery in the 1940s, gangliosides have been associated with a number of biological processes, such as growth, differentiation, and toxin uptake. Hypotheses about regulation of these processes by gangliosides are based on indirect observations and lack a clear definition of their mechanisms within the cell. The first insights were provided when a reduction in cell proliferation in the presence of gangliosides was attributed to inhibition of the epidermal growth factor receptor (EGFR). Since that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 111 publications
4
90
0
1
Order By: Relevance
“…It is commonly known that gangliosides are associated or complexed with signal transducers such as small G-proteins, Src family kinases, tetraspanins, and integrins (28). The modulation of ganglioside expression can therefore have deep effects on receptormediated signaling, notably RTKs, and regulate cell growth through inhibition/activation of signal transduction pathways (15)(16)(17). For example, tyrosine kinase activity of EGFR is inhibited by the monosialoganglioside G M3 through carbohydrate-carbohydrate interactions of G M3 with GlcNAc terminated N-glycan on EGFR, without interfering with EGF binding (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly known that gangliosides are associated or complexed with signal transducers such as small G-proteins, Src family kinases, tetraspanins, and integrins (28). The modulation of ganglioside expression can therefore have deep effects on receptormediated signaling, notably RTKs, and regulate cell growth through inhibition/activation of signal transduction pathways (15)(16)(17). For example, tyrosine kinase activity of EGFR is inhibited by the monosialoganglioside G M3 through carbohydrate-carbohydrate interactions of G M3 with GlcNAc terminated N-glycan on EGFR, without interfering with EGF binding (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cellular ganglioside composition can modulate the activity of growth factor receptors, and consequently induce the activation of intracellular molecular pathways (15)(16)(17). In this context, the phosphorylation status of 42 RTKs was simultaneously examined using a phospho-RTK array in MDA-MB-231 cells.…”
Section: C-met Receptor Is Constitutively Activated In G D3 Synthase-mentioning
confidence: 99%
“…Studies on modulatory effects, initially observed with GM3 on EGFR tyrosine kinase [1], have been extended to effects of GM1, GD1a, GD1b, and GT1b on platelet-derived growth factor receptor [21,24], GM1 and plasmalopsychosine on nerve growth factor receptor [23,25], and GM3 and sialyl-nLc4 on insulin receptors [22,26]. Therefore, such glycosphingolipid effects can be considered as common in growth factor and hormone receptors, in general (for review see [27,28]). …”
Section: Discussionmentioning
confidence: 99%
“…1 Gangliosides are also key signaling molecules of pivotal biological processes, including cellular recognition and adhesion, receptor signal transduction, growth regulation, and differentiation. [4][5][6] In addition, they are important messengers of the adaptive responses to stress such as apoptosis. Under stress conditions that dramatically increase their intracellular concentration, gangliosides can initiate the induction of an apoptotic program.…”
Section: Introductionmentioning
confidence: 99%